HUBUNGAN ANTARA DUKUNGAN ORANG TUA DENGAN MOTIVASI BELAJAR SISWA SEKOLAH - Sendi Mulia Wigunasti Sendi; Jeslyn Nurarifah Jeslyn; Fatonah Restiana Fatonah; Rahma Keisha Mustika Rahma; Fatimatul Khoeriyah Tri Nurjannah Fatimatul; Khansa Sabrina Hijriyati Khansa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The role of parents has a significant impact on children's learning success, particularly at the elementary school level, where children still require consistent attention, support, and family involvement. At this stage, students need guidance, encouragement, and mentorship to foster their enthusiasm and intrinsic motivation for learning. This study aims to examine the relationship between parental support and the learning motivation of elementary school students, with a specific focus on children's developmental needs during the early stages of formal education. The research employed a descriptive qualitative approach using a literature review method. This method was selected because it provides a comprehensive overview of how parental support influences students' learning motivation, based on findings from prior research. Data were obtained by reviewing literature from written sources, including scientific journals, books, articles, and other credible documents relevant to the research topic. The analysis was conducted descriptively through content analysis, which involved reading, assessing, and synthesizing information from various references to develop a more precise understanding of the relationship between parental support and learning motivation among elementary school students. The findings indicate that parental support plays a crucial role in enhancing students' learning motivation. Evidence from multiple studies demonstrates that parental attention, supervision, provision of learning resources, and emotional support significantly bolster children's enthusiasm and perseverance in the learning process. In line with educational theory, the family serves as a primary factor in helping children achieve optimal learning outcomes. Therefore, this study recommends that parents engage more actively in their children's learning activities to maximize the development of their learning motivation.